Face Piercing (Body Art): Choosing Pleasure vs. Possible Pain and Posture Instability - Matheron, Eric; Kapoula, Zoi (Frontiers in Physiology, 2011)
Piercings (body art, i.e. with jewelry) are more and more widespread. They can induce various complications such as infections, allergies, headaches, and various skin, cartilage, or dental problems which will lead to economic effects on health-care systems. We draw attention to other possible side effects resulting from face piercing complications such as eye misalignment, decreased postural control efficiency, and nonspecific chronic back pain. We found that the origin was pierced jewelry on the face. Removing the jewelry restored eye alignment, improved postural control, and alleviated back pain in a lasting way. This observation is important for health; further investigations would be of interest.